Parametric analysis for the installation of solar dish technologies in Mediterranean regions - Poullikkas, Andreas (2010)
In this work a feasibility study is carried out in order to investigate whether the installation of solar dish technologies for power generation in Mediterranean regions is economically feasible. The study takes into account the available solar potential for a typical Mediterranean country, such as Cyprus, as well as all available data concerning the current renewable energy sources policy of the island, including the relevant feed-in tariff of 0.26€/kWh. In order to identify the least cost feasible option for the installation of the solar dish plant a parametric cost–benefit analysis is carried out by varying the solar dish plant capacity, the solar dish plant capital investment and the CO2 emissions trading scheme price. The results indicated that the installation of solar dish plants in Mediterranean regions is economically feasible only in some cases, when a feed-in tariff incentive scheme exists, and that the size and the capital cost of the solar dish power plant are critical parameters affecting the economic viability of the technology.